Mobile usability - Nielsen, Jakob, 1957-; Budiu, Raluca (America: New Riders, 2013)
How do we create a satisfactory user experience when limited to a small device? This new guide focuses on usability for mobile devices, primarily smartphones and touchphones, and covers such topics as developing a mobile strategy, designing for small screens, writing for mobile, usability comparisons, and looking toward the future. The book includes 228-full color illustrations to demonstrate the points. Based on expert reviews and international studies with participants ranging from students to early technology adopters and business people using websites on a variety of mobile devices, this guide offers a complete look at the landscape for a mobile world. Author Jakob Nielsen is considered one of the world's leading experts on Web usability. He is the author of numerous best-selling books, including Prioritizing Web Usability and the groundbreaking Designing Web Usability, which has sold more than 250,000 copies and has been translated in 22 languages.
Includes index.
Keywords: Mobile computing; Web site development; Application software -- Development; User interfaces (Computer systems)